RESIDENCES SATISFACTION TOWARDS SERVICE QUALITY PROVIDED BY BOGOR LOCAL GOVERNMENT - Adi Kuswanto; Teddy Oswari; Budi Setiawan (Universitas Gunadarma, 2012)
The lowest local government as a frontline government has some crucial duties includes residences administration, village development, residences identity, land administration, and other duties. Up to present, the performance of the lowest local government is measured based on the regulation, but has never been measured based on the perception of its residences that have had service directly. The objective of the study are(1) to explore whether there is a differences between the perception and the expectation of the residences towards the service quality provided by the lowest local government; (2) to analyze the effect of service quality of the lowest local government on the satisfaction of the residences. The sampling method used in the research is stratified random sampling and collect 681 residences that have ever dealt with the lowest local government. The service quality was measured by comparing expectation and perception in which using six dimensions namely tangiable variable, reliability, responsiveness, assurance, empathy, and competence. The result of the study shows that the perception of residences on service quality is lower than their expectation. The service quality that affects on the residences satisfaction is tangiable, reliability, responsiveness, and competence variables. Assurance and empathy variables did not affect residences satisfaction. Keyword: Service, quality, government, satisfaction, residences